Unsteady flow and heat transfer due to a suddenly stopped continuous moving surface - Devi, S.P. Anjali; Asir, A. Alwyn; Thiyagarajan, M. (Computer Assisted Methods in Engineering and Science, 2023)
An approximate solution for the problem of unsteady flow and heat transfer caused by a suddenly stopped continuous moving surface and its gradual cooling has been obtained by solving the non-linear governing equations with the implicit finite difference scheme. Stability and convergence of the scheme are first verified. Then, the influence of the plate velocity, Prandtl number, time of stopping of the plate t1 and the cooling constant on the flow pattern, temperature, wall shear stress and heat flux is analyzed. It is found that velocity, temperature, wall shear stress and heat flux decrease in time. When the plate moves faster, fluid velocity, wall shear stress and heat transfer intensity are augmented whereas temperature goes down. The Prandtl number increases and the cooling constant reduces temperature and heat flux.